Carrageenan Raw Material Supply Projection in The Seaweed Production Center Area in Takalar Regency, South Sulawesi Province - Hermalena, Leffy; Noer, Melinda; Nazir, Novizar; Hadiguna, Rika Ampuh (Business Review and Case Studies, 2024)
Background: The seaweed industry has experienced rapid growth, especially in the production of food, feed, biofuels, and biochemicals. Indonesia has become the largest exporter of fresh, frozen, and dried seaweed; However, carrageenan derivative products are still limited. The demand for seaweed continues to increase, but the supply of seaweed raw materials for carrageenan-derived products has not met international standards, so it has failed to meet the demand in full. Seaweed production is exported as raw materials, and its added value has not been enjoyed by farmers, producers, local governments, and other stakeholders. The demand for carrageenan, especially as a raw material for the food industry, is increasing, which emphasizes the importance of seaweed supply.Purpose: This research aims to manage the supply of seaweed as raw material for carrageenan derivative products in the seaweed production center area in Laikang Village, Takalar Regency.Design/methodology/approach: This study uses qualitative analysis of interactive models Miles, Huberman, and Saldana. Techniques used include semi-structured interviews, where the implementation is more flexible to identify problems openly. Respondents were asked to provide more detailed information and ideas, which were then observedFindings/Results: The results of the study show that the management of seaweed supply in Laikang Village is sufficient in terms of quantity but still lacks in terms of quality according to the demand of the agroindustry.Conclusion: In order to improve seaweed quality through more inexpensive seeds, improved distribution, and eco-friendly practice training, government help is essential. Strategic planning in market research and supply management is emphasized in this study, which projects the seaweed supply for carrageenan derivatives in Laikang. While downstream processing regulations can optimize economic potential by minimizing the export of raw materials, effective supplyOriginality/value (State of the art): This study makes an original contribution by investigating a problem that is not clearly defined, poorly understood, or under-investigated (exploratory), thereby gaining a better understanding of the problems that exist in the supply of carrageenan raw materials in Laikang village., so that can provide an objective picture of the real conditions of the subjects being studied.Keywords: carrageenan, control, supply chain, production, quality of seaweed